2019
DOI: 10.1007/s42286-019-00017-6
|View full text |Cite
|
Sign up to set email alerts
|

Fully Nonlinear Potential Flow Simulations of Wave Shoaling Over Slopes: Spilling Breaker Model and Integral Wave Properties

Abstract: A spilling breaker model (SBM) is implemented in an existing two-dimensional (2D) numerical wave tank (NWT), based on fully nonlinear potential flow (FNPF) theory and the boundary element method (BEM), in which an absorbing surface pressure is specified over the crest of impending breaking waves (detected based on a maximum front slope criterion) to simulate the power dissipated during breaking. The latter is calibrated to match that of a hydraulic jump of parameters identical to local wave properties (height,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 93 publications
(223 reference statements)
2
26
0
Order By: Relevance
“…Grilli et al (1997) showed that the model could accurately predict breaking crest elevations, breaker index, and breaker types for solitary waves of various incident height propagating over mild to steep slopes. Finally, Grilli et al (2019) show that the model also accurately simulates the shoaling and propagation of periodic waves over a bar similar to that considered here. B9-r 97.2 1.43 0.7 2 10 0.57 0.08 0 0 Blenkinsopp and Chaplin (2007) Note.…”
Section: Appendix A: Sensitivity Of Local Geometric Parameters Used Imentioning
confidence: 53%
“…Grilli et al (1997) showed that the model could accurately predict breaking crest elevations, breaker index, and breaker types for solitary waves of various incident height propagating over mild to steep slopes. Finally, Grilli et al (2019) show that the model also accurately simulates the shoaling and propagation of periodic waves over a bar similar to that considered here. B9-r 97.2 1.43 0.7 2 10 0.57 0.08 0 0 Blenkinsopp and Chaplin (2007) Note.…”
Section: Appendix A: Sensitivity Of Local Geometric Parameters Used Imentioning
confidence: 53%
“…The implementation and validation of wave breaking dissipation methods have been presented for the fully nonlinear potential flow solver whispers3D in the case of two dimensional waves. Among the various breaking models presented in the literature, three existing dissipation methods were implemented here: HJ and HJf, based on the analogy between a breaking wave and a hydraulic jump (Guignard and Grilli, 2001;Grilli et al, 2019), and an eddy viscosity-like formulation of the dissipation (Kennedy et al, 2000). Three initiation criteria for wave breaking were also compared.…”
Section: Resultsmentioning
confidence: 99%
“…(3). The first method (denoted HJ in the following) uses an analogy with a hydraulic jump propagating over a flat bottom to estimate a pressure term D = −P surf /ρ, with ρ the water density (Guignard and Grilli, 2001;Grilli et al, 2019). The zone where the pressure is applied extends on both sides of the breaking wave crest between x f and x b (see Figure 1…”
Section: Wave Energy Dissipation Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The term introduced in the FSBC is computed by solving a differential equation derived by requiring that momentum is conserved as the waves break over a flat bottom. The second method, EHJ, is the implementation of the dissipative term proposed by Guignard and Grilli (2001) and Grilli et al (2019). This term is constructed such that it produces negative work proportional to the work done by a hydraulic jump with wave characteristics similar to those of the breaking wave.…”
Section: Discussionmentioning
confidence: 99%